Fleckenstein's hypothesis revisited: excessive myocardial calcification after prolonged high dose catecholamine treatment: a case report. Issue 4 (14th November 2018) - Dederer, Juliane; Custodis, Florian; Fries, Peter; Böhm, Michael
Abstract: Background: Myocardial calcification after prolonged highly dosed catecholamine treatment has been described experimentally. Here, we demonstrate myocardial calcifications by high-dose catecholamine treatment leading to chronic heart failure in patients. Case summary: A 62-year-old Caucasian woman presented with central pulmonary embolism, developing acute heart failure, and cardiogenic shock. Twenty-six days of high-dose norepinephrine treatment had to be administered to maintain circulation. After 74 days of intensive care treatment, the patient fortunately recovered but was readmitted to emergency ward because of dyspnoea and congestion. Computed tomography pulmonary angiography ruled out recurrence of pulmonary embolism, but depicted massive intramural cardiac calcifications, which were not present before treatment. Coronary angiography showed normal coronary arteries, and myocardial biopsy excluded infectious myocarditis. There was no evidence for sarcoidosis, thyroid disease, tuberculosis, or hyperparathyroidism. Oral heart failure treatment was initiated and at the 7 week follow-up the patient remained symptomatic with New York Heart Association functional Class III, while right and left ventricular function had recovered. Discussion: Prolonged activation of the heart by catecholamines leading to myocardial calcifications has first been examined experimentally by Fleckenstein et al . Herein, we are able to show, that this can occur in clinical situations. Careful dosing of catecholamines and early use of non-catecholamine-based haemodynamic support is recommended to avoid consecutive impairment of heart function and heart failure.